Penyelundupan Hukum Perkawinan di Bawah Umur Melalui Permohonan Itsbat Nikah di Pengadilan Agama - Nur Latifah Hanum; Shania Anwar; Siah Khosyiah (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2023)
Underage marriage is still a phenomenon in Indonesia. Law Number 16 of 2019 has determined that the minimum marriage limit for women and men is 19 years, providing a way for early marriage to apply for marriage dispensation. However, there are still many underage marriages performed under the hands without going through marriage dispensation and then asking for marriage itsbath to the Religious Court. According to the author, this is a legal smuggling to legalise early marriage. The number of judges who still grant this case is undoubtedly the focus of research. This research is empirical juridical by looking at phenomena in society associated with existing regulations and theories of legal smuggling, as well as methods of collecting data through observation and from documents obtained. The results of this study found that underage marriage problems seem to need to be taken seriously because they are prone to legal smuggling, considering that initially, itsbath nikah was only intended for the community for the reasons mentioned in article 7 paragraph (3) of the Compilation of Islamic Law. So judges, especially in religious courts, must start improving. If the judge can reduce the number of itsbath applications against underage marriage, then they have been able to contribute substantive justice to provide welfare for the community. This certainly makes a benchmark for the community not to carry out underage marriages without court permission and, at the same time, an effort to close the faucet of underage marriage in Indonesia. Thus, it is hoped that early marriage can be suppressed. In the future, the government will be able to produce regulations to provide criminal sanctions for perpetrators of early marriage, along with the change in the minimum age of marriage.